González Palacios, Carlos (comp.). Reflexiones sobre la democracia y el Estado de derecho en el mundo contemporáneo. Lima: ESAN, 2020 - Calero Ponce, María Victoria (2020)
This work is an important compilation effort - and in most cases, translation work - made up of eleven research papers by legal experts German, French, and Peruvian on legal issues related to the notions of democracy and the rule of law. Each contribution, which takes the form of an academic reflection of approximately ten pages, yields account of a reality from the specialty of each author in matters as different, but complementary, as the fight against corruption, the public administration in its relationship with the citizen or, more The contributions of the Lüth jurisprudence of the Peruvian Constitutional Court, which expresses that the Constitution of values acquires its legitimacy not because it is based exclusively on the will of the people, but on the universal of human dignity. All this makes this publication, probably, one of the most recent theoretical values for the theory of law public, so its reading is recommended to researchers and students.